2019
DOI: 10.1002/maco.201810696
|View full text |Cite
|
Sign up to set email alerts
|

The combination of minimally invasive electrochemical investigations and FTIR‐spectroscopy to analyze atmospheric corrosion product layers on zinc

Abstract: The present work describes the combination of electrochemical investigations by using a gel-type electrolyte with Fourier-transformed infrared spectroscopy to investigate partially extremely thin corrosion product films on titanium-zinc. The gel pad method enables the determination of corrosion relevant parameters such as the potential and the linear polarization resistance without altering the corrosion product layers, which are extremely prone to re-dissolution when freshly formed. Complementary infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…R L determined by linear polarization does not equal the pure R p as determined by fitting of EIS results. As a sum of all resistances, R L contains the electrolyte resistance, the different layer resistances, charge transfer resistance, and the resistance of the corrosion product film according to Langklotz et al [2] Thus, R L is in accordance with the sum of all resistances determined by EIS fitting since an analogous behavior in dependence of coating type and artificial aging time can be seen for all investigated samples. Valet et al have shown that R L values correspond well to EIS results and to the overall protective ability of zinc coatings and their respective corrosion products.…”
Section: Annexmentioning
confidence: 75%
See 4 more Smart Citations
“…R L determined by linear polarization does not equal the pure R p as determined by fitting of EIS results. As a sum of all resistances, R L contains the electrolyte resistance, the different layer resistances, charge transfer resistance, and the resistance of the corrosion product film according to Langklotz et al [2] Thus, R L is in accordance with the sum of all resistances determined by EIS fitting since an analogous behavior in dependence of coating type and artificial aging time can be seen for all investigated samples. Valet et al have shown that R L values correspond well to EIS results and to the overall protective ability of zinc coatings and their respective corrosion products.…”
Section: Annexmentioning
confidence: 75%
“…A Gamry Instruments Interface 1000 potentiostat/galvanostat was used as the measuring system. The influence of the iR drop in the gel electrolyte can be neglected for the measurement setup, according to the results of Langklotz et al [2] Table 1. Types of zinc coating, information on the type of post-treatment, and coating thickness.…”
Section: Measurement Setupmentioning
confidence: 99%
See 3 more Smart Citations